PENENTUAN INTERVAL PERAWATAN MESIN PRODUKSI UNTUK MENINGKATKAN AVAILABILITY MELALUI ANALISIS KEANDALAN - Kristinawati, Eti (Department Industrial Engineering, University of Muhammadiyah Malang, 2001)
Productivity in a production system is ar important problem and having many factors influence it such as machine condition. With getting machine order, the realibility value is also going to decrease so that machine component will get trouble that will decrease the machine productivity indirectly.